1997
DOI: 10.1006/viro.1997.8817
|View full text |Cite
|
Sign up to set email alerts
|

In VitroInfection and Replication of Hepatitis E Virus in Primary Cynomolgus Macaque Hepatocytes

Abstract: An in vitro model was developed to replicate hepatitis E virus (HEV) in normal primary cynomolgus macaque hepatocytes using a hormonally defined, serum-free medium formulation. Primary hepatocytes were infected in tissue culture following isolation by collagenase treatment of liver wedge biopsy material. Viral replication was monitored by a highly strand-specific reverse transcription-polymerase chain reaction (RT-PCR) assay, which could detect the positive- and negative-strands of HEV RNA independently in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 17 publications
2
31
0
1
Order By: Relevance
“…Furthermore, the high-titered anti-ORF3 antibody used in the immunofluorescence assays did not neutralize wild-type virions (data not shown) in agreement with a previous report that anti-ORF3 failed to neutralize HEV in a cynomolgus primary hepatocyte culture system (18). These data strongly suggest that the protein encoded by ORF3 is either not present in or is not an essential component of virions.…”
Section: Figsupporting
confidence: 90%
“…Furthermore, the high-titered anti-ORF3 antibody used in the immunofluorescence assays did not neutralize wild-type virions (data not shown) in agreement with a previous report that anti-ORF3 failed to neutralize HEV in a cynomolgus primary hepatocyte culture system (18). These data strongly suggest that the protein encoded by ORF3 is either not present in or is not an essential component of virions.…”
Section: Figsupporting
confidence: 90%
“…Since HEV is presumably transmitted by the fecal-oral route, it is unclear how the virus reaches the liver, and an extrahepatic site(s) of replication would be a possible explanation (2,37). Primary hepatocytes are the only known sites of HEV replication (43,44). In a preliminary study with naturally infected pigs, we found that positive-strand HEV RNA was detectable in a number of tissues, even after viremia was cleared (X. J. Meng et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…HEV cannot be cultured routinely, although it has recently been propagated in primary macaque hepatocytes (33,34) and a virus resembling HEV has been cultured in A549 cells (13). As a result, studies on HEV protein synthesis, processing, and assembly have been limited to heterologous gene expression systems.…”
Section: Hismentioning
confidence: 99%